Analisis Price,Service Quality Dan Desain Interior Terhadap Kepuasan Serta Dampaknya Pada Loyalitas Konsumen (Studi Kasus Ayam Penyet Cindelaras) - Juliani Pohan (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of price, service quality, and interior design on satisfaction and its impact on consumer loyalty (Case study of Cindelaras Penyet Chicken). The population in this study were people who had visited the Ayam Penyet Cindelaras restaurant. The sampling technique used was simple random sampling. The research data were obtained by distributing research questionnaires about price, service quality, interior design on satisfaction and their impact on consumer loyalty to 60 respondents. The results of data analysis show that partially interior design has a positive effect on satisfaction where the value of tcount (2.661)> t table (1.295) with a significant level of 0.000 <0.10, partially price has a positive effect on customer loyalty where tcount (3.178)> t table (1.295) with a significant level of 0.002 <0.10, partially satisfaction has a positive effect on consumer loyalty where the value tcount (3,851)> ttable (1,295) with a significant level of 0.000 <0.10, simultaneously price, service quality, interior design and satisfaction have a positive effect on customer loyalty where the value of Fcount (8.132)> Ftable (2.54) with a significant level of 0.000 <0.10.